2015
DOI: 10.1037/xan0000048
|View full text |Cite
|
Sign up to set email alerts
|

Occasion setting during a spatial-search task with pigeons.

Abstract: A spatial task was used to investigate if a stimulus could set the occasion for responding to a landmark. Pigeons were trained with a positive occasion setter (OS; a colored background display) signaling the contingency between a landmark (LM; visual patterned stimulus) and the location of a rewarded response. The two most common tests of an OS (transfer tests and post-training extinction of the OS) were then conducted. In Experiment 1, two occasion setting pairs were trained (+←XA/YB→+/A-/B-) with unique spat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 49 publications
2
7
0
Order By: Relevance
“…and decision confidence (how likely). This dissociation has also been observed in other learning paradigms (Balsam, Drew, & Yang, 2002; Gallistel & Gibbon, 2000; Gallistel, Mark, King, & Latham, 2001; Leising et al, 2015; Ruprecht et al, 2014). Said another way, it is as if following extinction the pigeons still knew where the target should be, given the presence of the landmark, but were not as confident as to whether the target would be there.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…and decision confidence (how likely). This dissociation has also been observed in other learning paradigms (Balsam, Drew, & Yang, 2002; Gallistel & Gibbon, 2000; Gallistel, Mark, King, & Latham, 2001; Leising et al, 2015; Ruprecht et al, 2014). Said another way, it is as if following extinction the pigeons still knew where the target should be, given the presence of the landmark, but were not as confident as to whether the target would be there.…”
Section: Discussionsupporting
confidence: 71%
“…Associative processes are phylogenetically ancient, present in all animal phyla except Porifera (e.g., sponges), and underlie a wide range of learning phenomena, such as conditioned flavor preference and aversion, conditioned reflexes, sexual conditioning, timing, evaluative conditioning, and skill acquisition (Domjan, 2005). Blaisdell and colleagues, among others, have accumulated evidence that associative processes contribute to spatial learning across many foraging tasks, including the acquisition of spatial control by a landmark (Spetch, 1995), conditioned inhibition (Leising, Sawa, & Blaisdell, 2012), sensory preconditioning (Sawa, Leising, & Blaisdell, 2005), blocking (Leising, Wong, Ruprecht, & Blaisdell, 2014; see also Rodrigo, Chamizo McLaren, & Mackintosh, 1997), overshadowing (Leising, Garlick, & Blaisdell, 2011; see also Chamizo, Manteiga, Rodrigo, & Mackintosh, 2006; Spetch 1995), and occasion setting (Leising, Hall, Wolf, & Ruprecht, in press). In these studies, punctate, visual landmarks served as spatial discriminative stimuli that signal the locations of a target instrumentally connected to a hidden food goal.…”
mentioning
confidence: 99%
“…More important, despite the differences in absolute amounts of transfer obtained, Bonardi’s, Holland’s, and Rescorla’s (e.g., Rescorla, 1991a, 1991b) data fall on the same continuum: little or no transfer after training in a single occasion setting task, more (but seldom complete) transfer across targets of other occasion setters, and even after subjects are trained on multiple occasion setting tasks, little or no transfer to separately trained targets (e.g., Bonardi, 1998; Bonardi & Hall, 1994). This general pattern is found in many conditioning preparations and species (e.g., Baeyens et al, 2004; Cleland, Ruprecht, Lee, & Leising, 2017; Leising et al, 2015; Roper, Chaponis, & Blaisdell, 2005; Skinner et al, 1998).…”
Section: Content Of Learning In Occasion Settingmentioning
confidence: 60%
“…In the section “Temporal factors,” we showed that occasion setting is more likely to emerge when the feature and target are noncontiguous and discontinuous, such that the feature provides information whether reinforcement will occur and the target informs when it will occur. An analogous “whether-where” distinction may be made when cues are spatially separated, for example in landmark tasks, in which a feature in one location signifies whether reinforcement (or escape) is available, but responding must be directed toward one or more spatially noncontiguous locations (Leising et al, 2015; Ruprecht, Wolf, Quintana, & Leising, 2014).…”
Section: Conditions For the Establishment Of Occasion Settingmentioning
confidence: 99%
“…Stability has been argued to be a critical variable in recruiting mapping systems (O'Keefe & Nadel, 1978, p. 95, see also Kneirim & Hamilton, 2011, and some behavioural studies have demonstrated that spatial learning is only possible when landmarks are geometrically stable (Biegler & Morris, 1993Cheng, 1988). Although subsequent studies showed that stability was not a prerequisite for spatial learning per se (Hogarth, Roberts, Roberts, & Abroms, 2000;Leising, Hall, Wolf, & Ruprecht, 2015;, it was later found that learning based on an unstable landmark did not require a functioning hippocampus (Pearce et al, 1998) but did require the dorsolateral striatum (Kosaki et al, 2015; see also Auger, Mullally, & Maguire, 2012;Auger, Zeidman, & Maguire, 2015 for evidence of neural sensitivity to spatial stability in humans). In a number of studies that have examined cue competition between boundaries and landmarks, the boundaries of the arena are always stable, whereas the landmarks are unstable.…”
Section: Introductionmentioning
confidence: 99%